Analisis Kerentanan Lahan Bantaran Sungai Way Mesuji Dengan Pendekatan Deskriptif Kuantitatif - Putra, Muhammad Hakiem Sedo; Mashuri, Mashuri (Jurnal Teknik Sipil, 2026)
This study aims to analyze the vulnerability of riverbank land along the Way Mesuji River using a descriptive quantitative approach. Riverbank land vulnerability is a critical issue related to natural resource management and flood disaster mitigation. The study identifies vulnerability factors, including land use, physical land conditions, and flood risk. Data were collected through field surveys, remote sensing, and spatial analysis using GIS software. The findings indicate that the level of land vulnerability along the riverbanks varies, with some areas showing high vulnerability due to unsustainable human activities and fragile geological conditions. These results provide a valuable foundation for disaster risk mitigation planning and more sustainable environmental management in the Way Mesuji Riverbank area.